Natural language processing with Python - Bird, Steven; Klein, Ewan.; Loper, Edward (Sebastopol, CA : O'Reilly, 2009)
This is an introduction to natural language processing, which supports a variety of language technologies, from predictive text and email filtering to automatic summarization and translation.
Na koricama :"Analyzing text with the natural language toolkit".
Str. 449-458: Bibliografija. Kazala.
Keywords: Python - Računalni programski jezik; Računalna lingvistika; Obrada prirodnog jezika